Saberes y prácticas de las madres sobre el estado nutricional de Pre-escolares de la Escuela Rosa Josefina Burneo. - Cartuche Morocho, Flor Magaly (2013)
The present investigative work has as objective: to determine the knowledge and practical of the mothers and their relationship on the nutritional state, of pre-school the-ace of the school "Rosa Josefina Burneo" that allows the construction of an educational proposal in nutrition. The methodology that was used, is a Study of Descriptive Type, because it is described as the knowledge and practical that the mothers possess they have influenced in the nutritional state of the children and girls and Traverse, because one gives in a place and certain time, the universe constituted it 250 children and girls, of which one worked with a pre-school sample of 30, for we use it technical and instruments like the taking of having measured antropométricas weight, it carves, what allowed to determine the index of Corporal Mass (IMC), the observation guide that was good us to observe the lonchera sent to los/as niños/as and in turn the presence of the mothers was needed for the realization of the survey and socialization of the educational proposal, previous to the informed consent to the directress of the school. Once obtained the information you proceeded to the tabulation of data, which are presented in simple charts and frequently crossed relative and percentage distribution, the same ones that took us to the following conclusions: that the Knowledge and Practical of the mothers, they have been replaced by the new customs, offering not very nutritious foods to the family, but this has not affected the nutritional state of the children and girls since the IMC he/she reveals that most of the children are in a state normal chord to the age. It is necessary to mention that the socialization of the educational proposal captured the attention and the mothers' interest has more than enough the pre-school children's nutrition.